2001
DOI: 10.1063/1.1400761
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of highly-conducting nitrogen-doped ultrananocrystalline diamond films

Abstract: Ultrananocrystalline diamond (UNCD) films with up to 0.2% total nitrogen content were synthesized by a microwave plasma-enhanced chemical-vapor-deposition method using a CH4(1%)/Ar gas mixture and 1%–20% nitrogen gas added. The electrical conductivity of the nitrogen-doped UNCD films increases by five orders of magnitude (up to 143 Ω−1 cm−1) with increasing nitrogen content. Conductivity and Hall measurements made as a function of film temperature down to 4.2 K indicate that these films have the highest n-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
325
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 478 publications
(349 citation statements)
references
References 23 publications
16
325
1
Order By: Relevance
“…While nitrogen-doped UNCD has been studied previously, [23][24] boron-doped UNCD (BD-UNCD) has not been systematically described and characterized in the literature. SwainÕs group reported the smoothest boron-doped diamond yet reported by adding a boron source (solid state BoronPlus and gas state B 2 H 6 ) to conventional Ar-rich UNCD gas system.…”
Section: Introductionmentioning
confidence: 99%
“…While nitrogen-doped UNCD has been studied previously, [23][24] boron-doped UNCD (BD-UNCD) has not been systematically described and characterized in the literature. SwainÕs group reported the smoothest boron-doped diamond yet reported by adding a boron source (solid state BoronPlus and gas state B 2 H 6 ) to conventional Ar-rich UNCD gas system.…”
Section: Introductionmentioning
confidence: 99%
“…The UNCD/a-C:H films prepared by CAPD have the following characteristics: (i) the production of p and n-type conduction accompanied by enhanced electrical conductivities is possible by B and N doping, respectively; (ii) they can be grown on foreign solid substrates; (iii) they can be grown at low substrate temperatures even on unheated substrates, while chemical vapor deposition (CVD) requires high substrate temperatures of more than 700 °C for the growth [23,24]. UNCD/a-C:H is a carbon-based semiconductor similarly to graphene, and it is a new candidate as spin transport materials.…”
Section: Introductionmentioning
confidence: 99%
“…The film consists of nanosized grains, which is similar to that deposited in Ar-rich H 2 /CH 4 /N 2 ambient [6,7,10]. Observed from the high magnification image (the inset of Fig.…”
mentioning
confidence: 97%
“…It was reported that n-type conductivity has been easily realized in the N-NDFs, since the N-atoms present predominantly in grain boundaries and introduce new electronic states associated with carbon S bonds and dangling bonds in the fundamental band gap [5]. The N-NDFs were generally prepared by introducing nitrogen (N 2 ) in the Ar/CH 4 /H 2 [6] or Ar/CH 4 [7] source gases. In these cases, N 2 is proposed as the n-type dopant, and Ar is favorable for generating more C 2 radical precursors to increase the nucleation density and consequently decrease the grain size to nanometer scale.…”
mentioning
confidence: 99%